2021
DOI: 10.3989/graellsia.2021.v77.303
|View full text |Cite
|
Sign up to set email alerts
|

Primera cita en África del caracol del cieno de Nueva Zelanda Potamopyrgus antipodarum (J.E. Gray, 1843) (Tateidae, Mollusca)

Abstract: Incluido recientemente entre las “cien peores” especies invasoras y siendo el tercero de los “peores moluscos invasores” en Europa, el caracol del cieno de Nueva Zelanda ha llegado a ser cosmopolita. Se comunica el primer hallazgo en el continente africano, en Marruecos. Se encontraron poblaciones establecidas de Potamopyrgus antipodarum en el humedal Low Moulouya, un Sitio Ramsar y un Sitio de Interés Biológico y Ecológico (SIBE), donde ocupa hábitats naturales y antropogénicos (manantial, río y canal artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Potamopyrgus antipodarum , colloquially known as the New Zealand mudsnail, is a globally invasive freshwater snail found in fresh and brackish waters in their native New Zealand range. These snails are a powerful model for biological invasion studies because they have recently invaded all continents except Antarctica (Alonso & Castro‐Díez, 2012 ; Collado, 2014 ; Taybi et al., 2021 ). In these novel environments, P .…”
Section: Introductionmentioning
confidence: 99%
“…Potamopyrgus antipodarum , colloquially known as the New Zealand mudsnail, is a globally invasive freshwater snail found in fresh and brackish waters in their native New Zealand range. These snails are a powerful model for biological invasion studies because they have recently invaded all continents except Antarctica (Alonso & Castro‐Díez, 2012 ; Collado, 2014 ; Taybi et al., 2021 ). In these novel environments, P .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ability to adapt to external stressors such as advantageous reproductive strategy and competitive traits (Duft et al 2003; Alonso and Castro-Díez 2008), which encompass both sexual and parthenogenetic reproduction (Zaranko et al 1997;Dybdahl and Kane 2005). Potamopyrgus antipodarum has successfully spread across vast parts of Europe, North America, South America, Australia, Asia and Africa (Alonso and Castro-Díez 2008; Taybi et al 2021) where it has observed substantial ecological impacts on aquatic ecosystems. These successful invasion of this invasive species is facilitated by its ability to be transported through several taxa such as migratory birds (Boycott 1936;Lassen 1975;Ponder 1988) and sh (trout and perch) ( Indeed, to prevent an ecological pandemonium (Elton 1942) and to protect natural habitats and endemic species, it is crucial to take proactive measures and prioritize the allocation of resources (Tarkan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon that invasive species successfully invade new environments despite having a low genetic variance is called the "Genetic Paradox of Biological Invasion" (Estoup et al, 2016;Frankham, 2005;Kolbe et al, 2004). However, various studies found that not all invasive species show a lower genetic variability and that diversity differs a lot between species (Bossdorf et al, 2005;Dlugosch & Parker, 2008;Kolbe et al, 2004;Lee, 2002;terHorst et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand mud snail (NZMS) Potamopyrgus antipodarum is a particularly suitable invasive species to investigate genetic adaptation and phenotypic plasticity. This fresh and brackish water snail originates from New Zealand and was introduced to Australia, Europe, North America, Japan, Chile, and most recently reached northern Africa (Alonso & Castro‐Díez, 2012; Collado, 2014; Taybi et al, 2021). The NZMS had already been introduced to Europe by the mid‐19th century, probably in the ballast water of ships (Ponder, 1988; Smith, 1889).…”
Section: Introductionmentioning
confidence: 99%